Uso de tomografias computadorizadas de feixe cônico na mensuração e análise das vias aéreas superiores - Araújo, Saulo Queiroz de (2019)
Diagnostic evaluation with Cone Beam Computed Tomography (CBCT) has gained a considerable scope in clinical decisions, enhancing the strategies of resolution offered to patients. Several parameters, however, can influence the final result of the analysis. The objective of the present work is, therefore, to evaluate the reliability of the reproduction of the CBCT data in the analysis of the airways. For this purpose, a total of 50 patients were selected. The upper airways were delimited in their posterior region and segmented virtually into three anatomic regions (nasopharynx, oropharynx and hypopharynx), which had their volumes quantified and morphology compared by the superposition of images. Significant volume variation has observed in two segments of the airway, with repercussion in the total volume of the pharynx, but with high correlation indices between the measured values. The greatest constriction areas didn’t demonstrate reliability for reproduction in CBCT studies. Cervical posture and body mass do not appear to influence airway dimensions in CBCT. It can be concluded that the volumetric and linear quantifications are reproducible and reliable for comparative analyzes in the CBCT, which make them useful elements in the attributions of clinical and dental research.